K-Domain Technology: Constitutive Expression of a Blueberry Keratin-Like Domain Mimics Expression of Multiple MADS-Box Genes in Enhancing Maize Grain Yield - Song, Guo-qing; Han, Xue (Frontiers in Plant Science, 2021)
MADS-box genes are considered as the foundation of all agronomic traits because they play essential roles in almost every aspect of plant reproductive development. Keratin-like (K) domain is a conserved protein domain of tens of MIKC-type MADS-box genes in plants. K-domain technology constitutively expresses a K-domain to mimic expression of the K-domains of other MADS-box genes simultaneously and thus to generate new opportunities for yield enhancement, because the increased K-domains can likely prevent MADS-domain proteins from binding to target DNA. In this study, we evaluated utilizing the K-domain technology to increase maize yield. The K-domain of a blueberry’s SUPPRESSOR of CONSTITUTIVE EXPRESSION OF CONSTANS 1 (VcSOC1K) has similarities to five MADS-box genes in maize. Transgenic maize plants expressing the VcSOC1K showed 13–100% of more grain per plant than the nontransgenic plants in all five experiments conducted under different experimental conditions. Transcriptome comparisons revealed 982 differentially expressed genes (DEGs) in the leaves from 83-day old plants, supporting that the K-domain technology were powerful and multiple functional. The results demonstrated that constitutive expression of the VcSOC1K was very effective to enhance maize grain production. With the potential of mimicking the K-domains of multiple MADS-box genes, the K-domain technology opens a new approach to increase crop yield.